A facile and rapid sonochemical synthesis of monodispersed Fe3O4@cellulose nanocrystal nanocomposites without inert gas protection. Issue 4 (16th May 2018) - Low, Liang Ee; Tey, Beng Ti; Ong, Boon Hoong; Tang, Siah Ying
Abstract: Here, we proposed a rapid sonochemical in situ co‐precipitation approach to prepare Fe3 O4 @cellulose nanocrystal (MCNC) nanocomposites. Differed from conventionaly method, the proposed in‐situ co‐precipitation reaction was performed under atmospheric condition without N2 purging to yield the MCNC. The results from FTIR analysis confirmed the formation of MCNC through the chemical interaction between the Fe ions of Fe3 O4 nanoparticles (MNP) with the surface hydroxyl groups of CNC. The absence of typical Fe2 O3 Raman spectral peak (730 cm −1 ) indicated no occurrence of oxidation of MNP to undesired maghemite. Based on TGA results, the MNP loading on the MCNC composites was found to be 6 wt% higher than those produced under typical N2 protection, giving rise to a higher magnetivity. Results revealed that the use of ultrasound (US) horn in place of conventional mechanical stirrer led to the production of the radical species that accelerated the nucleation, growth and dispersibility of MNPs on CNC fibres, which thus shortened the reaction times to 5 min. The findings suggest that the proposed sonochemical synthesis without inert N2 purging could be an alternative facile and efficient approach to fabricate well‐dispersed MCNC nanocomposites that hold great potential for biomedical applications.